Witnesses' memory for events and faces under elevated levels of intoxication. Issue 7 (9th August 2018) - Altman, Christopher M.; Schreiber Compo, Nadja; McQuiston, Dawn; Hagsand, Angelica V.; Cervera, Jiselle
ABSTRACT: Research on alcohol and witness memory has burgeoned over the last decade. However, most studies have tested participants at relatively low breath alcohol concentration (BAC) levels, unrepresentative of those encountered by officers in the field. To examine how higher intoxication levels might impair witness memory for events and faces, the current research tested participants' ability to recall a mock crime at elevated BAC levels (>.08%). The BAC levels of bar patrons ( N  = 138) were recorded before witnessing a video-taped mock crime. Participants were then interviewed using free recall and cued questions and shown a six-person target-present or target-absent lineup. Results show that alcohol negatively affected both the quantity and quality of recall. Regardless of question format, alcohol also reduced the percentage of accurate information elicited from witnesses; however, only cued questions increased the percentage of inaccurate information reported. Intoxication had no effect on identification accuracy. These findings suggest that the encoding and storage systems for faces and events may be impacted differently by alcohol. Our results also highlight the importance of including higher BAC levels when examining the effects of alcohol on witness memory.